Design considerations for a mobile robot with end effector - Zhang, Kaiyan (2019)
The research in this dissertation is based on the foundation of robot technology, and the structural design of omnidirectional mobile robot with end effector is discussed. First, the advantages and disadvantages of various mobile robot platform design schemes are analyzed and discussed. Based on the analysis of different design schemes and the consideration of the robot operating environment, the structure of the omnidirectional mobile robot based on Mecanum wheel is designed. Secondly, the parameters of the wheel are analyzed. According to the design requirements of the mobile robot, a Mecanum wheel with a diameter of 152 mm was selected. Third, the design of the drive motor and the reduction gearbox was calculated and analyzed. Through the analysis of different suspension system schemes, an independent suspension system is designed, which consists of a single longitudinal arm structure composed of springs and dampers. Fourthly, from the perspective of kinematics, the influence of the layout of the Mecanum wheel on the controllability of the mobile platform is calculated and analyzed, and the optimal "O" layout is determined. Fifth, the kinematics analysis of the mobile platform based on the Mecanum wheel provides theoretical support for the design of the motion control system.